2008
DOI: 10.1136/bjo.2007.130294
|View full text |Cite
|
Sign up to set email alerts
|

Disease severity and family history in keratoconus

Abstract: Presence or absence of family history is not associated with more severe clinical disease, at least when each marker for severity is considered independently. The results of this analysis are important for genetic studies of keratoconus in that it will allow recruitment of keratoconus patients across all stages of disease severity because it does not influence familial aggregation.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
25
3
1

Year Published

2010
2010
2022
2022

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 43 publications
(35 citation statements)
references
References 27 publications
2
25
3
1
Order By: Relevance
“…The genetic link in keratoconus is well known, but a family history is not linked to its severity. 60 Myopia has a generic link, but this does not influence progression. 61 Atopy is also a hereditary condition 62 as are corneal dystrophies 63 and dry eye has some family history association.…”
Section: Failure To Replace Lenses When Scheduledmentioning
confidence: 99%
“…The genetic link in keratoconus is well known, but a family history is not linked to its severity. 60 Myopia has a generic link, but this does not influence progression. 61 Atopy is also a hereditary condition 62 as are corneal dystrophies 63 and dry eye has some family history association.…”
Section: Failure To Replace Lenses When Scheduledmentioning
confidence: 99%
“…44,45 Although the majority of cases of KC are sporadic, reports of familial cases of KC are also common and aggregation of the disease in families is often observed. 46 The prevalence of KC in first degree relatives of index cases has been estimated to be 3.34%, notably higher than that in the general population. 47 Concordance is also high among monozygotic twins and a greater similarity of phenotype is observed in monozygotic twin pairs implying that genetic factors are likely to have a key role in the disease phenotype.…”
Section: Geneticsmentioning
confidence: 99%
“…60,[62][63][64] Other candidate genes screened in KC cohorts include TIMP3, 65 TGFBI, 66,67 ZEB1, 68 FLG 69 and several collagen genes. 46,70,71 Despite these efforts, potentially pathogenic variants have only been identified in a very small number of individuals with KC.…”
Section: Geneticsmentioning
confidence: 99%
“…10 In the same group, SzcotzkaFlynn et al concluded that presence or absence of family history is not associated with more severe clinical disease, however they found Caucasian ethnic group along with other risk factors could display higher prevalence of keraotconus in patient's family members. 19 In a study, conducted in Iran 300 eyes from 150 relatives of 45 patients with keratoconus. Of them, keratoconus was diagnosed in 14% and another 7.3% were considered suspicious of keratoconus.…”
Section: Discussionmentioning
confidence: 99%